Hyper-reactive PMNs in Fc gRIIa 131 H/H genotype periodontitis patients - E. A. Nicu (Blackwell Synergy, 2007)
Background: Receptors for the Fc part of IgG (FcgRIIa) on polymorphonuclear leukocytes (PMN) mediate phagocytosis and cell activation. Previous results show that one of the genetic variants of the FcgRIIa, the 131 H/H, is associated with more periodontal breakdown than the R/R. This may be due to hyper-reactivity of the H/H-PMNs upon interaction with bacteria. Aim: To study whether the FcgRIIa genotype modifies the PMN reactivity in periodontitis patients. Material and Methods: A cohort of 98 periodontitis patients was genotyped. From these, 10 H/H and 10 R/R consented to participate. PMNs were incubated with immune serum-opsonized Actinobacillus actinomycetemcomitans (A.a.). Phagocytosis, degranulation (CD63 and CD66b expression), respiratory burst and elastase release were assessed. Results: Patients of the H/H genotype showed more bone loss than those with the H/R or R/R genotype (p50.038). H/H-PMNs phagocytosed more opsonized A.a. than did R/R-PMNs (p50.019). The H/H-PMNs also expressed more CD63 and CD66b than did the R/R-PMNs (p50.004 and 0.002, respectively) and released more elastase (p50.001). Conclusions: The genotyping results confirm previous reports that more periodontal destruction occurs in the H/H genotype than in the H/R or R/R genotype. The functional studies indicate a hyper-reactivity of the H/H-PMN in response to bacteria, which may be one of several pathways leading to more periodontal breakdown.